2016
DOI: 10.26905/jkdp.v20i3.257
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Optimism and Debt Financing: Case Study on Indonesia Manufacturing Listed Firms

Abstract: Managerial's psychology can affect financial decision in the company. This paper analyzes the influence of managerial optimism on the debt financing by using regression analysis. The dependent variable in this paper is debt financing. The independent variable is managerial optimism and the control variable are firm value, firm size, and firm performance that are occurred in the previous period. The samples used in this study are manufacturing companies that listed in Indonesian Stock Exchange during 2010-2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Specifically, someone who has an extrovert personality with a more sensation-seeking attitude led to a more aggressive investment risk appetite (Wasiuzzaman & Edalat, 2016). Furthermore, the extrovert investor is also optimistic or even overestimate their investment return, so they can also have a higher investment risk appetite (Memarista, 2016) Concerning risk-taking behavior, the users of social networking sites tend to be more risk-taker person instead of to the person who has not Instagram (Fogel & Nehmad, 2009). Generally, the young risk-averse investor is being more silent observer about their colleague posts.…”
Section: Extroversion Personality and Investment Risk Appetitementioning
confidence: 99%
“…Specifically, someone who has an extrovert personality with a more sensation-seeking attitude led to a more aggressive investment risk appetite (Wasiuzzaman & Edalat, 2016). Furthermore, the extrovert investor is also optimistic or even overestimate their investment return, so they can also have a higher investment risk appetite (Memarista, 2016) Concerning risk-taking behavior, the users of social networking sites tend to be more risk-taker person instead of to the person who has not Instagram (Fogel & Nehmad, 2009). Generally, the young risk-averse investor is being more silent observer about their colleague posts.…”
Section: Extroversion Personality and Investment Risk Appetitementioning
confidence: 99%
“…The empirical relationship that has been carried out in Indonesia confirmed that debt has a negative influence on the value of the company. The studies were previously carried out by (Handriani et al, 2016;Memarista, 2016;Cheryta et al, 2018). Therefore, the fourth empirical proposition based on POT theory is: H4: Debt is negatively related to firm value…”
Section: The Effect Of Debt On Firm Valuementioning
confidence: 99%
“…It is because the managers believe that the company will get the benefit of them. The excessive assessment shows the manager optimism (Memarista, 2016). But, the firm cannot borrow the money to fund this expense.…”
Section: Sunk Cost Dilemma Behavior: the Contribution Marketing Expenmentioning
confidence: 99%